2017
DOI: 10.1016/j.quascirev.2017.06.032
|View full text |Cite
|
Sign up to set email alerts
|

Pottery use by early Holocene hunter-gatherers of the Korean peninsula closely linked with the exploitation of marine resources

Abstract: The earliest pottery on the Korean peninsula dates to the early Holocene, notably later than other regions of East Asia, such as Japan, the Russian Far East and Southern China. To shed light on the function of such early Korean pottery and to understand the motivations for its adoption, organic residue analysis was conducted on pottery sherds and adhered surface deposit on the wall of pottery vessels (foodcrusts) excavated from the Sejuk shell midden (7.7-6.8ka calBP) on the southeastern coast and the Jukbyeon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 37 publications
1
45
0
1
Order By: Relevance
“…Moreover, these culinary preferences persisted across Japan, even in warmer southerly areas where abundant nut and plant resources were increasingly available. Our earlier study from the Torihama shell midden site (5)(6)(7) in Japan indicates that this cognitive association persisted until at least the Middle Holocene, and may only have been truncated by the arrival of rice and millet agriculture approximately 2,500 cal BP. A similar association between early pottery and aquatic resources has also been identified in adjacent regions of East Asia such as Sakhalin Island (6,34,35) and the Korean Peninsula (5-7).…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…Moreover, these culinary preferences persisted across Japan, even in warmer southerly areas where abundant nut and plant resources were increasingly available. Our earlier study from the Torihama shell midden site (5)(6)(7) in Japan indicates that this cognitive association persisted until at least the Middle Holocene, and may only have been truncated by the arrival of rice and millet agriculture approximately 2,500 cal BP. A similar association between early pottery and aquatic resources has also been identified in adjacent regions of East Asia such as Sakhalin Island (6,34,35) and the Korean Peninsula (5-7).…”
Section: Resultsmentioning
confidence: 91%
“…A further 6.9% (50/722) have C 18 APAAs and TMTD, which are most likely aquatic in origin (i.e., partial aquatic biomarkers; Table 1), whereas the majority of samples (81%; 582/722) contained phytanic acid, the most frequent isoprenoid acid. Among the resources available to Japanese Pleistocene and Holocene hunter-gatherers, wild ruminants such as sika deer offer the only other major source of phytanic acid other than aquatic oils (7,24). To distinguish these, we examined the ratio of the two naturally occurring configurations, or diastereomers, of phytanic acid [3S,7R,11R,15-phytanic acid (SRR) and 3R,7R,11R,15-phytanic acid (RRR; Methods)].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dudd and Evershed 1998;Evershed et al 2002;Copley et al 2003;Evershed et al 2008;Dunne et al 2012;Debono Spiteri et al 2016). Likewise, aquatic products (Patrick et al 1985;Hansel et al 2004;Craig et al 2007;Hansel and Evershed 2009;Shoda et al 2017), plant oils and waxes denoting vegetable and plant oil consumption/ processing (Evershed et al 1991;Copley et al 2001a;Copley et al 2001b;Reber et al 2004;Copley et al 2005;Cramp et al 2011;Dunne et al 2016) and beeswax (Heron et al 1994;Charters et al 1995;Evershed et al 1997b;Regert et al 2001;Evershed et al 2003;Roffet-Salque et al 2015), resins, tars and bitumen (Beck et al 1989;Mills and White 1989;Evershed et al 1997a;van Bergen et al 1997;Urem-Kotsou et al 2002;Stern et al 2003;Buckley et al 2004;Stern et al 2008;Connan et al 2013;Brown et al 2014: Brettell et al 2014 have been identified in connection with a wide range of technological and cultural activities. On a broader scale, lipid residue analyses can provide insight into the domestication of plants and animals, the development of animal husbandry practices and ecological and environmental changes through time (Evershed 2008b;Evershed et al 2008;…”
Section: Introductionmentioning
confidence: 99%